2023
DOI: 10.1002/hed.27498
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative three‐dimensional scanning of head and neck surgical defects: Enhanced communication and documentation of harvested supplemental margins

Jun Yun,
Vivian Su,
Danielle Kapustin
et al.

Abstract: BackgroundWe have demonstrated the effectiveness of 3D resection specimen scanning for communicating margin results. We now address the corresponding surgical defect by debuting 3D defect models, which allow for accurate annotations of harvested supplemental margins.MethodsSurgical defects were rendered into 3D models, which were annotated to document the precise location of harvested supplemental margins. 3D defect scans were also compared with routine 2D photography and were analyzed for quality, clarity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We have previously described our work ow for 3D specimen scanning [5,12,13]. The complexity of large head and neck resections render them di cult to document, either by drawing or descriptions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously described our work ow for 3D specimen scanning [5,12,13]. The complexity of large head and neck resections render them di cult to document, either by drawing or descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Following videoconferencing to describe the margin results, the surgeon annotates 3D defect scans to document location and size of harvested supplemental margins. We have previously demonstrated that 3D defect scans are superior to standard conventional defect photography, as the defect scans are rotated in space to optimize documentation of supplemental margins [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations